The Characteristics of Local Dark Brown Waxy Sorghum Rice from Lamongan Due to the Different Polishing Frequency and Soaking Conditions - Rahmawati Rahmawati; Malika Husni Aulia; Shanti Pujilestari; Julfi Restu Amelia; Joni Munarso (Jurnal Ilmu Pertanian Indonesia, 2025)
Dark brown local glutinous sorghum has the potential to replace white rice because it has higher carbohydrate and dietary fiber contents and lower total sugar content. Sorghum has the disadvantages of hard seeds and astringency, which can be reduced by polishing and soaking. The aim of the research was to study the effect of the polishing frequency and soaking condition on sorghum seed with 2 research variables: (1) the polishing frequency [once and twice] and (2) soaking conditions [(1) 100°C water allowed to reach room temperature for 24 h; (2) 100°C water allowed to reach room temperature for 36 h; (3) baker's yeast 0.25% b/v at room temperature for 24 h; and (4) baker's yeast 0.25% b/v at room temperature for 36 h]. Rice quality was tested for hardness, elasticity, chewiness, stickiness, organoleptic properties, and antioxidant activity. Data was processed using ANOVA (α = 0.05) and Duncan’s Multiple Range Test. The results showed that the polishing frequency and soaking conditions affected the hardness, elasticity, chewiness, and stickiness of sorghum rice. The best sample was found to be twice-polished dark brown glutinous sorghum rice, with a 100 °C water soaking condition, and allowed to reach room temperature for 36 h. The sorghum rice had a hardness of 2,578.6 ± 1,044.4 gf, elasticity of 48.24 ± 0.20%, chewiness of 0.3622 ± 0.00, stickiness of (-76.88 ± 0.76) gs, with antioxidant activity of 0.0041 mg/g (strong), which panelists liked and similar with rice from the parameters of color (score 5.0 ± 0.2), aroma (score 4.5 ± 0.1), texture (score 4.8 ± 0.1), and taste (score 4.5 ± 0.1). Keywords: dark brown waxy sorghum, Lamongan city, local commodity, polishing frequency, soaking condition